Plasma cholesteryl ester transfer protein is predominantly derived from Kupffer cells. Issue 6 (28th August 2015) - Wang, Yanan; van der Tuin, Sam; Tjeerdema, Nathanja; van Dam, Andrea D.; Rensen, Sander S.; Hendrikx, Tim; Berbée, Jimmy F.P.; Atanasovska, Biljana; Fu, Jingyuan; Hoekstra, Menno; Bekkering, Siroon; Riksen, Niels P.; et al.
Abstract : The role of Kupffer cells (KCs) in the pathophysiology of the liver has been firmly established. Nevertheless, KCs have been underexplored as a target for diagnosis and treatment of liver diseases owing to the lack of noninvasive diagnostic tests. We addressed the hypothesis that cholesteryl ester transfer protein (CETP) is mainly derived from KCs and may predict KC content. Microarray analysis of liver and adipose tissue biopsies, obtained from 93 obese subjects who underwent elective bariatric surgery, showed that expression of CETP is markedly higher in liver than adipose tissue. Hepatic expression of CETP correlated strongly with that of KC markers, and CETP messenger RNA and protein colocalized specifically with KCs in human liver sections. Hepatic KC content as well as hepatic CETP expression correlated strongly with plasma CETP concentration. Mechanistic and intervention studies on the role of KCs in determining the plasma CETP concentration were performed in a transgenic (Tg) mouse model expressing human CETP. Selective elimination of KCs from the liver in CETP Tg mice virtually abolished hepatic CETP expression and largely reduced plasma CETP concentration, consequently improving the lipoprotein profile. Conversely, augmentation of KCs after Bacille‐Calemette‐Guérin vaccination largely increased hepatic CETP expression and plasma CETP. Also, lipid‐lowering drugs fenofibrate and niacin reduced liver KC content, accompanied by reduced plasma CETP concentration. Conclusions : Plasma CETP is predominantly derived from KCs, and plasma CETP level predicts hepatic KC content in humans.(Hepatology 2015;62:1710–1722)